Contextual Classifier Ensemble for Predicting Customers Churn - Jakubczyc, Janina Anna (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2008)
Problem of customers churn is becoming more and more important for many companies. Looking for appropriate technique to support an effective identification of migrants as well as causes of the migration is the subject of this article. We present appealing approach, which is contextual classifier ensemble that can find acceptable solution for this difficult problem.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 25, s. 85-93